Role and participation of women in the establishment and implementation of international security policies - Marigonë Vrajolli (Academicus, 2018)
Women have long been excluded from peace and security processes, which include disarmament, despite being disproportionately affected by weapons. Emphasizing, the role of women in peace and security processes began to gain meaning only after 2000, when the United Nations Resolution, Resolution 1325 entered into force. In order for women to participate equally in such processes, the resolution emphasizes the necessity of women’s participation as agents of positive change and not as weak and powerless victims. Contributing to a society where women can live freely in harmony without being marginalized. The purpose of this paper is to explain the different roles that women have in creating security policies. Further, this paper explains the role of women in initiatives, peacekeeping and peace-building. The paper also explains the international mechanisms that promote the involvement of women in peace and security processes.